Aspek Hukum Liabilitas Public Figure Dan Upaya Perlindungan Terhadap Nama Dikaitkan Dengan Cancel Culture - Alycia, Clara (JATISWARA, 2022)
In Indonesia, cyberbullying is still considered very low because people think that hate speech is just criticism and advice for people who are criticized. Until finally this cancel culture action was mostly done by netizens and from the existence of this greatly affected their reputation. The legal problem that arises from the cancel culture is that many public figures have lost their reputations due to the emergence of unproven issues but their names and careers have been crossed out. The method used is the futuristic method. Regarding the restoration of the good name of public figures themselves, they can use criminal methods in the form of articles on defamation and the use of Article 27 Paragraph 3 of the ITE Law, but the use of these articles is still not effective, so there needs to be a review related to this in order to get clarity from these actions. Regarding the right to be removed, there is currently no more detailed regulation that discusses this matter. In addition, from these actions, the reputation of public figures greatly affects the brands that have made them brand ambassadors. For the community itself, it is expected to be able to see from 2 sides first by listening and seeing the evidence provided by the victim so that it does not just boycott or cancel the culture and by canceling the culture it will affect the reputation of the public figure. In addition, there is also a need for a review of specific laws or regulations to protect the post-cancellation culture that has not been proven for the good name of public figures and regarding the right to be forgotten, it is necessary to have clearer arrangements so that in practice it does not create ambiguity.